Stock assessment of tunas from the Indian seas - James, P S B R; Pillai, P P; Jayaprakash, A A; Yohannan, T M; Siraimeetan, Pon; Muthiah, C; Gopakumar, G; Pillai, N G K; Reuben, S; Thiagarajan, R; Koya, K P Said; Kulkarni, G M; et al. (Indian Journal of Fisheries, 2011)
Tunas constitute one of the importantmarine fisheries resources of our countrycontributing 1.5 to 2.0% of the total marinefish landings. The potential of this resourcehas been estimated to be 200 000 tonnes in theIndian EEZ. Popularly known as the 'chickenof the sea', tunas comprising of a number ofspecies are exploited all along the Indiancoasts.